PENGELOLAAN KEUANGAN SEDERHANA SYARIAH UNTUK PEDAGANG KECIL BERBASIS APLIKASI DIGITAL (Studi Kasus Pedagang Makanan di komplek Pondok Sunan Pandanaran Yogyakarta) - Mushawir, Mushawir; Setyaningsih, Erlyka; Nisa, Khoiriyatun (khidmatan, 2025)
This community service program aims to enhance basic sharia financial management literacy among small food vendors around the Sunan Pandanaran Islamic Boarding School Complex in Yogyakarta through the utilization of digital financial applications. Prior to the implementation, key challenges identified included inconsistent bookkeeping practices, the mixing of personal and business finances, and limited understanding of basic financial mathematics. The program employed a Participatory Action Research (PAR) approach, consisting of initial data collection, written interviews, and sharia financial education emphasizing the principle of trust (amanah) in financial recording, the separation of business and personal assets, and basic understanding of commercial zakat (zakat al-tijarah), along with basic financial mathematics training and technical assistance in using Google Sheets and BukuWarung applications. The results indicate an improvement in participants’ ability to record daily transactions, prepare simple profit–loss statements, and apply sharia-based financial management practices. Approximately 70% of participants were able to independently implement digital bookkeeping, although challenges related to digital literacy and internet connectivity remained. Overall, the program proved effective in improving financial governance and efficiency among small food vendors based on sharia financial principles.